Deciphering the emerging role of phytocompounds: Implications in the management of drug-resistant tuberculosis and ATDs-induced hepatic damage - Mohammad Azam Ansari; Shoaib Shoaib; Mohammad N. Alomary; Hissana Ather; Shaik Mohammad Asif Ansari; Umme Hani; Yahya F. Jamous; Sami A. Alyahya; Jameela Naif Alharbi; Mohammad Azhar Imran; Shadma Wahab; Wasim Ahmad; et al. (Elsevier, 2023)
Tuberculosis is a disease of poverty, discrimination, and socioeconomic burden. Epidemiological studies suggest that the mortality and incidence of tuberculosis are unacceptably higher worldwide. Genomic mutations in embCAB, embR, katG, inhA, ahpC, rpoB, pncA, rrs, rpsL, gyrA, gyrB, and ethR contribute to drug resistance reducing the susceptibility of Mycobacterium tuberculosis to many antibiotics. Additionally, treating tuberculosis with antibiotics also poses a serious risk of hepatotoxicity in the patient's body. Emerging data on drug-induced liver injury showed that anti-tuberculosis drugs remarkably altered levels of hepatotoxicity biomarkers. The review is an attempt to explore the anti-mycobacterial potential of selected, commonly available, and well-known phytocompounds and extracts of medicinal plants against strains of Mycobacterium tuberculosis. Many studies have demonstrated that phytocompounds such as flavonoids, alkaloids, terpenoids, and phenolic compounds have antibacterial action against Mycobacterium species, inhibiting the bacteria's growth and replication, and sometimes, causing cell death. Phytocompounds act by disrupting bacterial cell walls and membranes, reducing enzyme activity, and interfering with essential metabolic processes. The combination of these processes reduces the overall survivability of the bacteria. Moreover, several phytochemicals have synergistic effects with antibiotics routinely used to treat TB, improving their efficacy and decreasing the risk of resistance development. Interestingly, phytocompounds have been presented to reduce isoniazid- and ethambutol-induced hepatotoxicity by reversing serum levels of AST, ALP, ALT, bilirubin, MDA, urea, creatinine, and albumin to their normal range, leading to attenuation of inflammation and hepatic necrosis. As a result, phytochemicals represent a promising field of research for the development of new TB medicines.